Does Homeschooling Fit Students With School Attendance Problems? Exploring Teachers’ Experiences During COVID-19 - Havik, Trude; Ingul, Jo Magne (Frontiers in Education, 2021)
Attending school on a regular basis and completing school is usually seen as a precondition for students’ academic, emotional, and social learning and development. However, some students struggle with school attendance problems (SAPs) for a myriad of reasons. Homeschooling is a topic of concern in long-term or problematic SAP cases. Some scholars claim that school absenteeism might increase and be maintained, while others argue that homeschooling may reduce students’ anxiety associated with school attendance. Regardless, homeschooling is often an intervention for academic learning and/or as a part of gradual reintegration to school for SAP students. Moreover, homeschooling/home education/home tuition is not a new phenomenon and is an intervention for students with long-term sickness. When schools in many countries closed from the middle of March 2020 caused by the COVID-19 pandemic, all students were homeschooled. This gave us the opportunity to investigate homeschooling more closely. In the current study, teachers’ thoughts and experiences of homeschooling for students with SAPs prior to the pandemic are investigated. The main aim was to gain more insight into and knowledge about homeschooling: does it work for SAP students? Practical implications of homeschooling for SAP students are discussed.